The Implementation of the Reading Guide Method to Improve Literal Reading Comprehension Outcomes in Fourth-Grade Elementary School Students - Abd Hafid; Sitti Rahmi; SURIANI (Journal of Primary Education Innovation and Research, 2026)
This study is Classroom Action Research that aims to describe the improvement of literal reading comprehension skills among fourth-grade students at SD Negeri 79 Ujung Tanah through the implementation of the Reading Guide method. The subjects of this study were 17 fourth-grade students of SD Negeri 79 Ujung Tanah and one fourth-grade homeroom teacher. The research setting was SD Negeri 79 Ujung Tanah. Data collection techniques used observation and tests. The data analysis techniques included data reduction, data description, and conclusion drawing. The results of the study showed that in Cycle I, only 10 students, or 59%, achieved the mastery score, while 7 students, or 41%, had not yet achieved mastery. After learning improvements were carried out in Cycle II by optimizing the Reading Guide method, students’ learning outcomes increased. A total of 14 students, or 82%, successfully achieved the mastery score, while only 3 students, or 18%, had not yet achieved mastery. The conclusion of the study shows that the implementation of the Reading Guide method can improve the reading comprehension skills of fourth-grade students at SD Negeri 79 Ujung Tanah.